2022
DOI: 10.1007/s00382-022-06201-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the uncertainties in the hydrological projections in Korean river basins using dynamically downscaled climate projections

Abstract: How the added value of dynamically downscaled climate variables can be transferable to the hydrological impact assessment has been a long standing issue. This study investigates the potential benefit of highresolution climate data locally tailored over South Korea in terms of the reduction of uncertainties in hydrological projections. For this purpose, a large ensemble consisting of three Global Climate Model (GCM) projections and their downscaling products with different resolutions (i.e., 20 and 5 km), and f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…[Colour figure can be viewed at wileyonlinelibrary.com] and 3.5 C. In this process, climate models AWI-CM-1-1-MR and MPI-ESM1-2-LR exhibit considerable uncertainty in DNN and RNN processes; however, LSTM shows less uncertainty in these models. Furthermore, earlier studies have suggested that uncertainty is reduced after applying ANN and statistical downscaling in climate models (Qiu et al, 2022;Okkan et al, 2023).…”
Section: Spatial Heterogeneity Of Spatial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…[Colour figure can be viewed at wileyonlinelibrary.com] and 3.5 C. In this process, climate models AWI-CM-1-1-MR and MPI-ESM1-2-LR exhibit considerable uncertainty in DNN and RNN processes; however, LSTM shows less uncertainty in these models. Furthermore, earlier studies have suggested that uncertainty is reduced after applying ANN and statistical downscaling in climate models (Qiu et al, 2022;Okkan et al, 2023).…”
Section: Spatial Heterogeneity Of Spatial Performancementioning
confidence: 99%
“…As precipitation is a fundamental component in the water cycle, a comprehensive outlook is essential for managing water systems under changing climate (Sachindra & Perera, 2016). Studies has shown that the downscale high‐resolution data will significantly improve in the simulation of meteorological and hydrological variables (Ghosh and Mujumdar, 2008; Qiu et al, 2022; Singh & Mall, 2023). According to Okkan et al (2023) downscale GCM outputs through the ANN structures will provide sufficient simulation accuracy for climate uncertainty and climate impact study.…”
Section: Introductionmentioning
confidence: 99%
“…They cannot adjust the inter-variable dependencies, which are important for representing physical processes and estimating compound hazards. It was not until quite recently that the multivariate BC technique was considered and proposed (e.g., Bárdossy & Pegram, 2012;Cannon, 2018;Mehrotra & Sharma, 2015, 2016Robin et al, 2019;Vrac, 2018), and they have been applied to various climate change impact studies (Dieng et al, 2022;Meyer et al, 2019;Qiu et al, 2022;Zscheischler et al, 2019). Although it is intuitively recognized that multivariate BC could be more suitable for dealing with climate variables characterized by a strong physical linkage in nature, an unambiguous assessment of univariate and multivariate BC methods is essential to understand the potential limitations of individual methods and to avoid misleading application.…”
mentioning
confidence: 99%